Evaluation of shear bond strength and shear stress on zirconia reinforced lithium silicate and high translucency zirconia - Amanda Maria de Oliveira Dal Piva; João Paulo Mendes Tribst; Marco Antonio Bottino (Universidad de Concepción., 2018)
This study evaluated the shear stress distribution on the adhesive interface and the bond strength between resin cement and two ceramics. For finite element analysis (FEA), a tridimensional model was made using computer-aided design software. This model consisted of a ceramic slice (10x10x2mm) partially embedded on acrylic resin with a resin cement cylinder (Ø=3.4 mm and h=3mm) cemented on the external surface. Results of maximum principal stress and maximum principal shear were obtained to evaluate the stress generated on the ceramic and the cylinder surfaces. In order to reproduce the in vitro test, similar samples to the computational model were manufactured according to ceramic material (Zirconia reinforced lithium silicate - ZLS and high translucency Zirconia - YZHT), (N=48, n=12). Half of the specimens were submitted to shear bond test after 24h using a universal testing machine (0.5 mm/min, 50kgf) until fracture. The other half was stored (a) (180 days, water, 37ºC) prior to the test. Bond strength was calculated in MPa and submitted to analysis of variance. The results showed that ceramic material influenced bond strength mean values (p=0.002), while aging did not: YZHT (19.80±6.44)a, YZHTa (17.95±7.21)a, ZLS (11.88±5.40)b, ZLSa (11.76±3.32)b. FEA results showed tensile and shear stress on ceramic and cylinder surfaces with more intensity on their periphery. Although the stress distribution was similar for both conditions, YZHT showed higher bond strength values; however, both materials seemed to promote durable bond strength